La sociologie du travail allemande : entre engagement empirique et ambivalence théorique - Bénédicte Zimmermann (La Nouvelle Revue du Travail)
After a modicum of initial institutionalisation under the Weimar Republic, German sociology of work established itself during the 1960s, largely revolving around themes such as industrial relations, technology and skilled industrial labour. The affirmation of a subjectivation paradigm during the 1980s broadened the spectrum of analysis to encompass the agency-related and embodied dimensions of work. Although these various research orientations remain relatively compartementalised, they have hitherto shared a unifying framework based on Marxist references and an aspiraton to offer a critical diagnosis of society. It remains that this critical ambition is currently in search of a new theory of society, even as the dominant mode for funding contract research leaves little leeway for broad theoretical investigations.Después de un comienzo de institucionalización bajo la República de Weimar, la sociología del trabajo alemana se desarrolla a partir de los años 1960 en torno a las temáticas de las relaciones profesionales, de la técnica y del trabajo obrero calificado. La afirmación en los años 1980 de un paradigma de la subjetivación amplía el espectro de análisis hacia la dimensión activa y encarnada del trabajo. Aunque estas diferentes orientaciones de investigación comunican poco entre ellas, encuentran un marco unificador en la referencia marxista y la ambición de contribuir a un diagnóstico crítico de la sociedad. Pero esta ambición crítica está actualmente en busca de una nueva teoría de la sociedad, mientras que la forma dominante de financiamiento contractual de la investigación deja poca libertad para obras teóricas de envergadura.